AN ANALYSIS OF SLICE-OF-LIFE VIDEO ADVERTISEMENT STRUCTURES IN LEICA AND FUJIFILM - Ivana Larissa Nirwasita; Fatma Anyassari, Nugrahaningtyas (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
Leica and Fujifilm are two well-known camera brands that use a slice-of-life advertising style, which emphasizes everyday problems and portrays their products as solutions. However, there has been limited research on the linguistic features of this type of advertisement. This study analyzed the structure of 24 slice-of-life video advertisements by Leica and Fujifilm posted on YouTube in 2024. This study aims to identify the structures used in these advertisements. The research employed a qualitative case study as the research method. Intra-coder reliability was conducted twice to ensure the credibility of the findings. The results revealed five mandatory structures: headline, problem, solution, features to benefit, and speaker’s introduction, which can be rearranged flexibly except for the headline. This research benefits novice copywriters, especially non-native ones, in writing advertising copy for high-involvement products in English.